Variasi Jumlah Koil Dengan 2 Busi Terhadap Peforma Yamaha Jupiter Z 110 CC - Santoso, Dedy, Ir. Sartono Putro, MT, Ir. Sarjito, MT, Ph.D (2016)
Both spark plugs and coils are important component in the ignition ssystem that will affect performance of the motorcycle combustion engine. This study will reveal the effect of the coils number with two spark plugs on the performance of the internal combustion engine with single cylinder four stroke through experimental testing. Performance parameters measured by the combustion engine torque, power, and specific fuel consumption. This research begins with modifying the internal combustion cylinder head into two holes of spark plug. A dynotets set was used in the experimental in order of test both torque and power. Specific fuel consumption data were obtained with several measuring tools such as burrettes, stopwatch, and tachometer. Both calculated variations data of single coil and two coils are compared to standard design. The result show that the standard ignition produces that the highest torque of 7,21 Nm with the fuel consumption up to 0,105 kg/Hp.h.